Urogynaecology and you : a handbook for women with bladder disorders, womb and vaginal Prolapse - Han, How Chuan (World Scientific, 2010)
This easy-to-use, concise, yet informative book deals with a comprehensive range of urogynaecological problems and explores solutions to these problems. It is written by a team of experienced and expertly trained urogynaecologists. The book is aimed at helping patients understand the common gynaecological conditions and the possible treatment options. It encourages further questions from patients who want to know more about the common conditions.